Potentiometric investigation of specific ionic effects on interactions between bovine serum albumin and weak polyelectrolytes - Mutka, Sanela (Array, 2008)
Abstract: The effect of salt on the behaviour of bovine serum albumin (BSA) in solution and on the interactions between BSA and the weakly charged polyelectrolytes poly(allylamine hydrochloride) and poly(dimethylaminoethylmethacrylate) was investigated by potentiometric titrations. Titrations of pure BSA solution and of the BSA solution with the addition of polyelectrolyte were performed in the presence of different salts. Three electrolytes having the same anion and a different cation were used, lithium chloride, sodium chloride, and caesium chloride. The corresponding base served as titrant. Experiments were performed at four electrolyte concentrations. The titration curves showed a strong influence of ionic strength and the electrolyte type. The cation effect was found to be in accordance with the Hofmeister series